Real-time Sampling of Particulate Matter Smaller than 2.5 µm from Amazon Forest Biomass Combustion - Costa, Maria Angélica Martins [UNESP]; Carvalho Júnior, João Andrade de; Soares Neto, Turíbio gomes; Anselmo, Edson; Santos, José Carlos Dos; Lima, Bruno de Araújo; Kura, L. T. U. [UNESP]; Santos, J. C. (Pergamon-Elsevier B.V. Ltd, 2012)
Particle size distribution from forest biomass combustion is an important parameter as it affects air quality, global climate and human health. There have been several studies that relate emission of 2.5e10 mm particulates and their effects on human health. The objective of this study was to sample particulates smaller than 2.5 mm from Amazon forest biomass burning in laboratory and field experiments. Sampling was carried out using three instruments: two DataRAM 4 (model DR 4000) and a Cascade Impactor. Isokinetic probes were used for sampling in the stacks, and an omnidirectional instrument was used for field sampling. The field experiment was conducted in a 4 ha Amazon forest test site in the state of Acre, in Brazil. Ignition, flaming and smoldering combustion phases were analyzed. Results were obtained in terms of particle size distribution and concentration. Comparison of laboratory and field experiments showed that particle size distributions were similar in both cases. Particle sizes obtained in the laboratory ranged from 0.05 to 0.8 mm; in the field experiment, sizes varied from 0.03 to 0.3 mm. Average concentrations in the laboratory and in the field were 185 mg m 3 and 350 mg m 3 , respectively. It is important to emphasize that those results were obtained throughout the burning process and the diameters sampled were smaller than 2.5 mm.
Keywords: Ultra-fine particulate matter; Real-time sampling; Amazon forest fires